Electroanalytical detection of zinc in whole blood - Kruusma, J; Banks, C; Nei, L; Compton, R (2004)
Three different electroanalytical techniques for the determination of zinc in blood are investigated. The direct determination in diluted blood via anodic stripping voltammetry at glassy carbon and the use of Nafion-coated glassy carbon mercury electrodes are shown to lack the necessary sensitivity whereas an acoustically assisted double extraction followed by sono-ASV using a glassy carbon electrode is found to be rapid, reliable and sensitive. © 2004 Elsevier B.V. All rights reserved.